Interest in and use of person-centred pharmacy services - a Swiss study of people with diabetes - Noura Bawab; Emilie Zuercher; Tania Carron; Léonie Chinet; Olivier Bugnon; Jérôme Berger; Isabelle Peytremann-Bridevaux (BMC, 2021)
Abstract Background Diabetes is one of the most important chronic diseases and affects 9% of the world's population. To support these people in the day-to-day management of their treatments, pharmacies can offer professional pharmacy services. These are defined as one or more actions organized or provided in a pharmacy to optimize the process of care, with the goal of improving health outcomes and the value of healthcare. Such services have to be tailored to the needs and interests of patients. This study aimed to evaluate interest in and use of pharmacy services among people with diabetes in the canton of Vaud, Switzerland. Methods This cross-sectional study analysed self-reported data from 790 people with diabetes included in the CoDiab-VD cohort. Questions focused on sociodemographic and economic characteristics, diabetes and its management, and interest in and use of pharmacy services related to (1) medication intake and adherence and (2) diabetes and general health. Descriptive analyses were first conducted. Logistic regression analyses were then performed for pharmacy services that were of interest to ≥50% of respondents. Results The mean age of participants was 66 years, and the sample included more males (59%) than females. The pharmacy services that interested the most respondents were individual interview, pill boxes or weekly pill boxes, treatment plans, checks of all medications, first medical opinions from pharmacists and counselling on devices. Factors significantly associated with interest in pharmacy services were being older, having a lower self-efficacy score, taking more than three medications and having a positive opinion about pharmacists. Conclusions This study provides key information on interest in and use of pharmacy services among patients with diabetes in Switzerland; it should help pharmacists individualize their services for patients.